Critically ill patients with infective endocarditis, neurological complications and indication for cardiac surgery: a multicenter propensity-adjusted study - Alexandre Gros; Benjamin Seguy; Guillaume Bonnet; Yves-Olivier Guettard; Xavier Pillois; Renaud Prevel; Arthur Orieux; Julien Ternacle; Sebastien Préau; Yoan Lavie-Badie; Elisabeth Coupez; Rémi Coudroy; et al. (Annals of Intensive Care, 2024)
Abstract Background The benefit–risk balance and optimal timing of surgery for severe infective endocarditis (IE) with ischemic or hemorrhagic strokes is unknown. The study aim was to compare the neurological outcome between patients receiving surgery or not. Methods In a prospective register-based multicenter ICU study, patients were included if they met the following criteria: (i) left-sided IE with an indication for heart surgery; (ii) with cerebral complications documented by cerebral imaging before cardiac surgery; (iii) with Sequential Organ Failure Assessment score ≥ 3. Exclusion criteria were isolated right-sided IE, in-hospital acquired IE and patients with cerebral complications only after cardiac surgery. In the primary analysis, the prognostic value of surgery in term of disability at 6 month was assessed by using a propensity score-adjusted logistic regression. Results 192 patients were included including ischemic stroke (74.5%) and hemorrhagic lesion (15.6%): 67 (35%) had medical treatment and 125 (65%) cardiac surgery. In the propensity score-adjusted logistic regression, a favorable 6-month neurological outcome was associated with surgery (odds ratio 13.8 (95% CI 6.2–33.7). The 1-year mortality was strongly reduced with surgery in the fixed-effect propensity-adjusted Cox model (hazard ratio 0.18; 95% CI 0.11–0.27; p < 0.001). These effects remained whether the patients received delayed surgery (n = 62/125) or not and whether they were deeply comatose (Glasgow Coma Scale ≤ 10) or not. Conclusions In critically ill IE patients with an indication for surgery and previous cerebral events, a better propensity-adjusted neurological outcome was associated with surgery compared with medical treatment.